Beyond Liver Disease: Non-Alcoholic Fatty Liver Disease and Advanced Liver Fibrosis in Kidney Disease - Han, Eugene (Diabetes & metabolism journal, 2022)
The epidemiological evidence suggests that NAFLD is an in dependent risk factor for albuminuria, and the severity of steatosis is correlated with albuminuria prevalence [5,6]. [...]advanced liver fibrosis is associated with proteinuria and increased urinary markers regardless of albuminuria presence [7,8]. Another Korean study demonstrated that the increased incidence of CKD in NAFLD did not indicate a direct association between NAFLD and CKD in diabetes subgroup analysis [13]. NOTES CONFLICTS OF INTEREST No potential conflict of interest relevant to this article was reported. 1.